2022
DOI: 10.3390/en15249620
|View full text |Cite
|
Sign up to set email alerts
|

Review of Current State-of-the-Art Research on Photovoltaic Soiling, Anti-Reflective Coating, and Solar Roads Deployment Supported by a Pilot Experiment on a PV Road

Abstract: The objective of this review paper is to provide an overview of the current state-of-the-art in solar road deployment, including the availability of anti-reflection and anti-soiling coating materials for photovoltaic (PV) technology. Solar roads are built using embedded PV panels that convert sunlight into electricity, which can be stored for later use. Prototypes of solar roads have been tested on various continents, but the lack of suitable PV materials has limited their effectiveness compared to conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
0
1
0
Order By: Relevance
“…In such a case, we also found that anti-PID could not mitigate the increase in temperature of the hotspots and could not resolve the output power losses caused by PV hotspots. The results of this study confirm that an anti-PID inverter is capable of preventing PID and, to some degree, other malfunctions in the PV module's performance (e.g., leakage of current or degradation in EVA [25][26][27][28][29]). As a result, it can provide an alternative solution to hotspot recovery.…”
Section: Thermographic Inspectionsupporting
confidence: 66%
“…In such a case, we also found that anti-PID could not mitigate the increase in temperature of the hotspots and could not resolve the output power losses caused by PV hotspots. The results of this study confirm that an anti-PID inverter is capable of preventing PID and, to some degree, other malfunctions in the PV module's performance (e.g., leakage of current or degradation in EVA [25][26][27][28][29]). As a result, it can provide an alternative solution to hotspot recovery.…”
Section: Thermographic Inspectionsupporting
confidence: 66%
“…In conclusion, it is crucial to be aware of the Alternatively, another effective method to detect cracks involves using electroluminescence (EL). This approach is performed by inducing current to the PV module, which causes the electrons in the solar cell to become excited in the conduction band and resulting in an EL image, as shown in Figure 4b [32]. Among the most important features of EL imaging is its utility in inspecting both small and large cells, specifically both solar cells and PV modules [33].…”
Section: Solar Pv Module Cracks Detection Techniquesmentioning
confidence: 99%
“…The electroluminescence (EL) imaging technique is an effective method to inspect the performance of solar cells [19]. To achieve this, it is imperative to apply a biased current to the cell.…”
Section: El Imagingmentioning
confidence: 99%